Oxidative stress and cardiac contractility: a double edge sword? - Zavala, Maite Raquel (2021)
The stretch of cardiac muscle increases developed force in two phases. The first phase occurs immediately after stretch and is the expression of the Frank–Starling mechanism, while the second one or slow force response (SFR) occurs gradually and is due to an increase in the calcium transient amplitude. Previously, we have shown that the SFR is the mechanical manifestation of an autocrine/paracrine mechanism activated by wall stretch involving growth factors-triggered reactive oxygen species (ROS) formation, and followed by redox-mediated cardiac Na+/H+ exchanger (NHE1) activation leading to an increase in the Ca2+ "transient" amplitude. Recent own experiments assigned a role to thioredoxin-1 (“TRX1”, an important cellular antioxidant enzymatic system) in the development of the SFR. Interestingly, cardiac hypertrophy and failure, two of the most important health problems in western societies, are both triggered by intracellular signals triggered by myocardial stretch, being oxidative stress a critical step for its progression. Remarkably, experimental evidence has revealed that TRX1 overexpression negatively regulates cardiac hypertrophy. In this scenario, this short review was meant to briefly discuss the physiological, but potentially pathological, role of oxidative stress following myocardial stretch.